2007
DOI: 10.2353/jmoldx.2007.060182
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Differentiation Correlates with Absence of EGFR Mutation and Presence of KRAS Mutation in Lung Adenocarcinomas with Bronchioloalveolar Features

Abstract: Somatic mutations in the epidermal growth factor receptor gene (EGFR) are detected in a subset of lung adenocarcinomas, particularly bronchioloalveolar carcinoma (BAC) and adenocarcinoma with bronchioloalveolar features (AWBF), and correlate with clinical response to tyrosine kinase inhibitors (TKIs). In contrast, lung adenocarcinomas refractory to TKIs often have activating mutations in KRAS but lack EGFR mutations. Some adenocarcinomas have mucinous histology, but the clinical and molecular significance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
131
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 37 publications
(50 reference statements)
14
131
3
1
Order By: Relevance
“…38 Most importantly, statistical analysis failed to show any significance of this subtype. Similar to Finberg et al, 37 we found a strong correlation of mucinous differentiation in mixed subtypes of adenocarcinomas and KRAS mutations. 40 Marchetti et al 50 showed the same correlation in mucinous types of bronchioloalveolar carcinoma.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…38 Most importantly, statistical analysis failed to show any significance of this subtype. Similar to Finberg et al, 37 we found a strong correlation of mucinous differentiation in mixed subtypes of adenocarcinomas and KRAS mutations. 40 Marchetti et al 50 showed the same correlation in mucinous types of bronchioloalveolar carcinoma.…”
Section: Discussionsupporting
confidence: 76%
“…35,36 In contrast, mucinous differentiation was associated with KRAS mutations in some studies. 37,38 This variety of morphological interpretations reflects the lack of consistency in the interpretation of the World Health Organization criteria for classifications of lung tumors. Furthermore, different types of samples, including surgical resection and cytology specimens, were used for morphological analysis.…”
mentioning
confidence: 99%
“…8 In this new classification (Table 1) there are several major changes for surgically resected tumors: (1) the term bronchioloalveolar carcinoma (BAC) is no longer used and the growth pattern of BAC is referred to as lepidic pattern; (2) adenocarcinoma in situ is proposed for small (r3 cm) solitary adenocarcinomas with pure lepidic growth lacking invasion; (3) minimally invasive adenocarcinoma (MIA) is proposed for small (r3 cm) lepidic predominant tumors with r0.5 cm of invasion; (4) invasive adenocarcinomas are now classified according to the predominant subtype after performing comprehensive histological subtyping with semiquantitative assessment of each subtype in 5% increments; 4 (5) micropapillary adenocarcinoma is added as a major subtype because of its poor prognostic significance in multiple studies of early stage lung adenocarcinoma; [9][10][11] (6) former mucinous BACs are now classified as invasive mucinous adenocarcinomas recognizing that most of these tumors will have invasive components, less expression of TTF-1, frequent KRAS mutations, characteristic CT finding primarily of consolidation rather than ground glass opacities, worse prognosis than non-mucinous lepidic predominant adenocarcinomas and lack of responsiveness to tyrosine kinase inhibitors; [12][13][14][15][16][17][18][19] and (7) clear cell and signet ring adenocarcinoma are recognized to represent cytological changes that occur in multiple histological subtypes rather than in separate histological subtype. 20,21 We sought to explore the prognostic significance of this classification in a large series of surgically resected stage I lung adenocarcinomas.…”
Section: A New Lung Adenocarcinoma Classification Is Being Proposed Bmentioning
confidence: 99%
“…EGFR and KRAS mutations were observed in 10%-30% of cases, with a higher frequency of EGFR mutations being found in Asians, in people who had no history of smoking, and in nonmucinous tumors (5). However, it has been found that the level of KRAS mutation is associated with smoking, being non-Asian, and invasive mucinous adenocarcinoma (19). A BRAF mutation rate of 1.9% was reported in nonsmokers with adenocarcinoma (18).…”
Section: Discussionmentioning
confidence: 99%